Perceptions and Challenges of Undergraduate EFL Students’ towards Audiobooks and Textbooks on the Xreading Website - Widodo, Jalu Wintang; Nugroho, Him’mawan Adi (IJLECR (International Journal of Language Education and Cultural Review), 2024)
Based on PISA literacy test in 2022, Indonesia gains rank 70 which 5 points higher than previous period in 2018. However, it still needs more efforts to maximize the level of students’ literacy in Indonesia. The use of X-reading as the web-based book technology becomes the alternative tools to improve EFL undergraduate students’ literacy level. This research aims to explore the undergraduate students’ perception and challenge in using audiobook and textbook, that are provided by Xreading website during extensive reading activity. This research is conducted to EFL undergraduate students through qualitative method and purposive sampling technique. Three undergraduate students in Surabaya are involved by using descriptive qualitative method. The use of audiobook and textbook in Xreading website have some positive and negative impacts for students in developing their literacy competence. Audiobook is able to improve the students’ listening skill and understand the unfamiliar vocabularies. However, it has some weaknesses such as it needs strong internet data and connection and cannot control the audio speed. The textbook gives the students experience as reading the physical book and the grammatical understanding. Nevertheless, textbook is more time consuming especially for students who have the lower reading skill. Hopefully, this research will be developed into the low level of education not only in undergraduate level, but also in the secondary school and this website expanded into the intensive reading.